The New College Vision and Laser Data Set - Smith, M; Baldwin, I; Churchill, W; Paul, R; Newman, P (2009)
In this paper we present a large dataset intended for use in mobile robotics research. Gathered from a robot driving several kilometers through a park and campus, it contains a five-degree-of-freedom dead-reckoned trajectory, laser range/reflectance data and 20 Hz stereoscopic and omnidirectional imagery. All data is carefully timestamped and all data logs are in human readable form with the images in standard formats. We provide a set of tools to access the data and detailed tagging and segmentations to facilitate its use.